One-pot synthesis of CdSe nanoparticles exhibiting quantum size effect within a sol-gel derived ureasilicate matrix - Gonçalves, L. F. F. F. (2014)
tThis paper describes the one-pot synthesis of CdSe nanoparticles (NPs) exhibiting quantum size effect,by the reaction between cadmium and selenosulfate ions in the presence of 3-mercaptopropyltri-methoxysilane (MPTMS), within a hybrid organic–inorganic xerogel material produced by sol–gel. Thehighly transparent, homogeneous and flexible xerogel matrix doped with the CdSe NPs was preparedusing an organically modified silicon alkoxide (3-isocyanatepropyltriethoxysilane) and a di-amine func-tionalized poly(ethylene oxide)/poly(propylene oxide) (Jeffamine ED-600), as precursors, which bysubsequent hydrolysis and condensation reaction formed a solid network. The influence of the molarratio between cadmium and selenosulfate ions and between cadmium ion and MPTMS in the opticalproperties of the nanocomposites was investigated. The materials were characterized by absorption,steady-state and time-resolved photoluminescence (PL) spectroscopy and by TEM. The absorption spec-trum showed the presence of CdSe NPs with quantum size effect. The PL studies showed the presence ofCdSe NPs with near band-edge emission. The developed method allows in a simple manner, at ambienttemperature, using inexpensive reagents and without the need of the previous synthesis of the NPs bycolloidal methods, the production of hybrid materials doped with semiconductor NPs showing quantumsize effect. The developed sol–gel process allows also the control of the optical properties of the obtainedCdSe NPs embedded within the network by adjusting the molar ratio between cadmium ion and MPTMSand between cadmium and selenium ions. The presence of NPs with near band-edge emission stabilizedwithin a solid matrix opens the perspective of practical applications that take advantage of the opticalproperties of NPs, in particular photophysical applications such as photoluminescent devices.